A Peer Counselling Model: Social Outreach - Guttman, Mary Alice Julius (Canadian Journal of Counselling and Psychotherapy, 2011)
A peer counselling model emphasizing outreach social activities and school community liaison for adolescents is presented. Evaluation of this model according to (1) counsellors' self reports, and (2) student clients' evaluations indicate that peer counsellors are perceived as highly effective in (1) social leadership, (2) group discussion, and (3) individual counselling roles. In addition, over 60 per cent of student clients indicated they sought counselling with 42 per cent seeking multiple contacts.